Implementasi Kurikulum Merdeka di Pendidikan Anak Usia Dini (PAUD): Tinjauan Kritis dari Perspektif Guru - Maya Lestari (PERNIK, 2024)
The Implementation of the Merdeka Curriculum in Early Childhood Education (ECE) presents unique challenges and opportunities in improving the quality of early childhood education in Indonesia. This article analyzes teachers' perspectives on the implementation of the Merdeka Curriculum, focusing on understanding, implementation, and impact of the curriculum. Through questionnaires and critical analysis, findings indicate that most teachers have a sufficient understanding of the Merdeka Curriculum, although there is still a need for better training and support. Implementation challenges include resource limitations, inadequate management support, and the expansion of new learning approaches. Nevertheless, the Merdeka Curriculum has had a positive impact on children's motivation to learn and parental involvement in education. In conclusion, with a collective commitment to improving the quality of PAUD education, the Merdeka Curriculum has great potential to provide innovation and optimal benefits for the development of children in Indonesia.